PENGARUH PAJAK PROGRESIF DAN DIGITALISASI TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI BANGKINANG - Priscilla Nanda Julita; Dwi Fionasari; Norra Isnasia Rahayu (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of progressive tax and digitalization on motor vehicle taxpayer compliance in Bangkinang. This research employs a quantitative approach. The population of the study consists of 442,941 motor vehicle taxpayers registered at the Samsat Office of Bangkinang. The sample size was determined using the Slovin formula, resulting in 100 respondents. The data used in this study consist of primary data obtained through questionnaires distributed to motor vehicle taxpayers in Bangkinang and secondary data derived from books and academic journals. Data collection was conducted using a questionnaire technique. The research variables include taxpayer compliance as the dependent variable, and progressive tax and digitalization as independent variables. Data analysis was performed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that progressive tax has no significant effect on taxpayer compliance, while digitalization has a positive and significant effect on motor vehicle taxpayer compliance. The coefficient of determination (R Square) is 0.339, indicating that progressive tax and digitalization simultaneously contribute 33.9% to taxpayer compliance, while the remaining 66.1% is influenced by other factors not examined in this study.